EVALUATION OF HYPOGLYCEMIC EFFECT OF ETHANOLIC EXTRACTS OF LEAF AND FRUIT OF T.DIOICA AND LEAF OF C.TERNATEA IN STREPTOZOTOCIN INDUCED DIABETIC RATS - Dr. R. KAVITHA (International Journal of Pharma and Bio Sciences, 2014)
Trichosanthes dioica and Clitoria ternatea were traditional plants that were used for the treatment of diabetes mellitus, stress and depressant. The present work was undertaken to evaluate the antihyperglycemic effect of individual and combined ethanolic extracts of these two different herbs to study the blood glucose level and the activities of some carbohydrate metabolizing enzymes in liver of normal and STZ-induced diabetic rats. The extracts were administered orally to the diabetic rats for 28 days, resulted in significant decrease of blood glucose and decrease the activities of glucose-6-phosphatase and fructose-1,6-bisphosphatase and increase the activities of glucokinase, pyruvate kinase and glucose-6-phosphate dehydrogenase. From the study it was revealed that combined plant extract was more effective for treating diabetes mellitus.